Adaptive responses to air pollution in human dermal fibroblasts and their potential roles in aging. Issue 10 (17th July 2021) - Reynolds, Wil J.; Bowman, Amy; Hanson, Peter S.; Critchley, Adam; Griffiths, Ben; Chavan, Bhaven; Birch‐Machin, Mark A.
Abstract: The damaging effects of air pollution on the skin are becoming increasingly researched and the outcomes of this research are now a major influence in the selection and development of protective ingredients for skincare formulations. However, extensive research has not yet been conducted into the specific cellular defense systems that are being affected after exposure to such pollutants. Research investigating the affected systems is integral to the development of suitable interventions that are capable of augmenting the systems most impacted by air pollutant exposure. The following studies involved exposing primary human dermal fibroblasts to different concentrations of particulate matter and analyzing its effects on mitochondrial complex activity, nuclear factor erythroid 2‐related factor 2 localization using immunocytochemistry and protein expression of electron transport chain complex proteins, sirtuin‐1 (SIRT1), and peroxisome proliferator‐activated receptor gamma coactivator‐1α (PGC‐1α) using western blotting. Particulate matter‐induced alterations in both mitochondrial complex protein and activity, indicating oxidative stress, which was also complimented by increased expression of antioxidant proteins GSTP1/2 and SOD2. Particulate matter also seemed to modify expression of the proteins SIRT1 and PGC‐1α which are heavily involved in the regulation of mitochondrial biogenesis and energy metabolism. Given the reported results indicating that particulate matter induces damage through oxidative stress and has a profound effect on mitochondrial homeostasis, interventions involving targeted mitochondrial antioxidants may help to minimize the damaging downstream effects of pollutant‐induced oxidative stress originating from the mitochondria.